Construction and validation of simulated scenarios in the emergency care of patients with chest pain - Mayara dos Santos Barbosa; Lívia Maria Lopes Ferreira; Raphael Raniere de Oliveira Costa; Rodrigo Guimarães dos Santos Almeida; Fábio da Costa Carbogim; Angélica da Conceição Oliveira Coelho (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To construct and validate clinical simulation scenarios for emergency care for patients with chest pain. Methods: A methodological study carried out in two stages: construction and validity. The construction took place through the survey of evidence from national and international literature. The validity stage took place through instrument assessment by judges, according to the Content Validity Index and application of a pilot test with the target audience. Fifteen judges with expertise in simulation, teaching and/or care participated in the research, in addition to 18 nursing students, in the pilot test. Results: Two scenarios of clinical simulation were constructed, and all the assessed items obtained a value above 0.80, showing evidence of validity, being considered instruments suitable for application. Conclusion: The research contributed to the development and validity of instruments that can be applied for teaching, assessment and training in clinical simulation in emergency care for patients with chest pain.